Toward strain resistant flexible organic thin film transistors - Jedaa, Abdesselam; Halik, Marcus (Applied Physics Letters, 2009)
We suggest a molecular design for small molecules as polycrystalline organic semiconductors in flexible organic thin film transistor applications, providing an improved stability during substrate bending. A stable operation of alkyl-substituted sexithiophens was obtained under strain up to ±2.5%. The stability relates to the flexibility of the alkyl chain substitution, scales with their chain length, and outperforms those of pentacene devices. These findings were independent from the underlying dielectric layer.